Bulky olefin epoxidation under mild conditions over Mo-based oxide catalysts - Gomes, Diana M. (2024)
Molybdenum-based epoxidation catalysts are among the most investigated since the homogeneous Mo-based catalytic process claimed by Halcon International Inc. for liquid phase olefin epoxidation (EPO). While homogeneous Mo-based catalytic technologies reached industrial implementation for olefin EPO, the same does not apply for heterogeneous Mo-based ones, which have not reached industrial implementation (e.g., to meet catalyst productivity and stability requirements). In this work, EPO nanocatalysts consisting of oxides possessing molybdenum and M = Ta, Nb or W, were prepared via a simple, versatile methodology. The influence of the material synthesis conditions on the material properties was investigated to meet superior catalytic performances. Promising Mo-based solid catalysts were obtained which promoted the EPO of relatively bulky olefins such as fatty acid methyl esters (methyl oleate, methyl linoleate), using tert-butyl hydroperoxide as oxidant under mild conditions; e.g., the materials Mo(75D)M-0.3 with M = Nb, W (20 min synthesis using 75 at.% Mo relative to M, and MoO2Cl2 as precursor), obtained in a fast synthesis of 0.3 h, led to 92-96 % epoxide selectivity at 84-95 % methyl oleate conversion, 70 °C. To the best of our knowledge, these are the first Mo,M oxides reported for these reactions.